Neutralizing antibody to Pseudomonas aeruginosa exotoxin in human sera: evidence for in vivo toxin production during infection. - Pollack, M (1976)
Antibody to Pseudomonas aeruginosa exotoxin was detected in human sera by using a cytotoxicity-neutralization assay. Serum antitoxin was present in high titer in all 14 patients who recovered from serious pseudomonas infections (log2 of 50% neutralization titer, mean +/- standard deviation = 6.0 +/- 1.2). In contrast, serum antitoxin was present in lower titer in four of seven patients with fatal pseudomonas infections (3.3 +/- 2.7, P less than 0.005), in 3 of 7 patients with non-pseudomonas infections (1.4 +/- 0.6 P less than 0.001), and in 6 of 14 normal control subjects (2.0 +/- 1.3, P less than 0.001). Fourfold or greater serum antitoxin rises were demonstrated in two survivors of acute infections, and toxin-neutralizing activity was associated with the immunoglobulin G fraction of human sera. Immunization of rabbits with purified exotoxin also induced high antitoxin titers.